MODEL PEMBINAAN IMAN REMAJA BERBASIS DIGITAL DALAM MENGHADAPI TANTANGAN ERA DIGITAL DI HKBP SIHANTANDOHAN - Butar-butar, Imelda; Sitorus, Dani; Silaban, Debora Oktalina; Sianturi, Ertile Tinen; Nainggolan, Israwana (Jurnal Pengabdian Multidisiplin Indonesia (JUPEMI), 2026)
This community service program was conducted in response to the declining participation of adolescents in church faith-development activities and the increasing challenges of uncontrolled digital media use among youth. The program aimed to analyze the condition of youth faith formation, identify major challenges in the digital era, and develop a contextual faith-development model at HKBP Sihantandohan Church. The method employed was a participatory empowerment approach involving 30 adolescents aged 13–19 years through three stages: preparation, implementation, and evaluation. Data were collected through observation, attendance records, questionnaires, and group reflection sessions. Program activities included digital-based Bible study, digital ethics workshops, group discussions, educational games, and social service activities. The results showed an increase in adolescent participation in worship and mentoring activities based on attendance comparisons before and after the program, accompanied by improved understanding of Christian values, character formation, and awareness of ethical social media use. The findings indicate that digital-based faith development can serve as an effective and relevant strategy for engaging Generation Z adolescents. Therefore, churches are encouraged to adopt contextual, integrative, and participatory approaches in strengthening youth spirituality and character in the digital era.